Protective effect of a Protein Epitope Mimetic CCR10 antagonist, POL7085, in a model of allergic eosinophilic airway inflammation. Issue 1 (December 2015) - Daubeuf, François; Jung, Françoise; Douglas, Garry; Chevalier, Eric; Frossard, Nelly
Abstract Background Potential involvement of the CCR10/CCL28 axis was recently reported in murine models of allergic asthma. If confirmed, blockade of the CCR10 receptor would represent an alternative to current asthma therapies. We evaluated the effect of a novel Protein Epitope Mimetic CCR10 antagonist, POL7085, in a murine model of allergic eosinophilic airway inflammation. Methods Mice were sensitized and challenged to ovalbumin. POL7085, a CCR10 antagonist (7.5 and 15 mg/kg), dexamethasone (1 mg/kg) or vehicle were administered intranasally once daily 1h before each allergen challenge. On day 21, airway hyperresponsiveness, bronchoalveolar lavage inflammatory cells and Th2 cytokines, and lung tissue mucus and collagen were measured. Results Allergen challenge induced airway hyperresponsiveness in vehicle-treated animals as measured by whole body barometric plethysmography, and eosinophilia in bronchoalveolar lavage. POL7085 dose-dependently and significantly decreased airway hyperresponsiveness (34 ± 16 %) and eosinophil numbers in bronchoalveolar lavage (66 ± 6 %). In addition, the highest dose of POL7085 used significantly inhibited lung IL-4 (85 ± 4 %), IL-5 (87 ± 2 %) and IL-13 (190 ± 19 %) levels, and lung collagen (43 ± 11 %). Conclusions The Protein Epitope Mimetic CCR10 antagonist, POL7085, significantly and dose-dependently decreased allergen-induced airway hyperresponsiveness and airway inflammation after once daily local treatment. Our data give strong support for further investigations with CCR10 antagonists in asthmatic disease.